Parents' Weekend. Photo 022 - Arkin, Sarah (Tufts Archival Research Center, 2008)
Parents' Weekend. Introduction to the Deans of the Undergraduate Schools Linda Abriola, dean of the School of Engineering, presents: ÃÃÃ¥ÃWater: Innovative Technology or Perpetual Stewardship?ÃÃÃ¥Ã Robert Sternberg, dean of the School of Arts and Sciences, presents: ÃÃÃ¥ÃLeadership, Intelligence, and Stupidity.ÃÃÃ¥Ã In Braker Hall 001.